ANALISIS MATERI HIDROLISIS GARAM DALAM BUKU TEKS PELAJARAN KIMIA SMA/MA KELAS XI BERDASARKAN KRITERIA TAHAP SELEKSI 4S TMD - Noti Zulita Midiana; Made Sukaryawan; Diah Kartika Sari (Chemistry Education Study Program Sriwijaya University, 2022)
This study is aims to analyze the salt hydrolysis material in the SMA/MA class XI textbooks based on the selection criteria of the 4S TMD. The selection of the 4S TMD used has criteria of the suitability of material with curriculum 2013, the truth of the concept, and influcation of values. The suitability of material with curicculum 2013 in term of breadth of the material an the depth of concept. Based of the result of the analysis of the breadth of material in textbook A there are 8 concept labels declared approprite. While the textbook B There are 8 concept labels which are stated to be approprite, and concept labels which is stated to be too broad. The results of the analysis of the depth of the concept of textbook A there is 1 concept that is declared approprite, 4 concept are not deepth, 3 concept are too deep. In the textbook B there are 2 concepts that are stated to be approprite, 3 concepts that are not deep enough, and 3 concepts are to deep. The results of the analysis of the truth of the concept of textbook A there are 2 concept labels which are stated according to the scientists, and 6 concept label which were stated not to be approprite. In the textbook B there are 8 concept labels which are stated to e scientifcally correct. The result of the analysis of the instillation of the value of textbook A there are 8 value that are instilled namely, religious, tolerance, democratic, friendly/communicative, hard work, curiosity, discipline, and responsibility. In the textbook B there are 7 values that are instilled namely, tolerance, democracy, friendly/communicative, hard work ,curiosity, discipline, and responsibility. The result of the selection analysis show that textbook B it is better than textbook A can be used in learning activities.